Challenges of Interpreting Frontal Neurons during Value-Based Decision-Making - Wallis, Jonathan D.; Rich, Erin L. (Frontiers in Neuroscience, 2011)
The frontal cortex is crucial to sound decision-making, and the activity of frontal neurons correlates with many aspects of a choice, including the reward value of options and outcomes. However, rewards are of high motivational significance and have widespread effects on neural activity. As such, many neural signals not directly involved in the decision process can correlate with reward value. With correlative techniques such as electrophysiological recording or functional neuroimaging, it can be challenging to distinguish neural signals underlying value-based decision-making from other perceptual, cognitive and motor processes. In the first part of the paper, we examine how different value-related computations can potentially be confused. In particular, error-related signals in the anterior cingulate cortex, generated when one discovers the consequences of an action, might actually represent violations of outcome expectation, rather than errors per se. Also, signals generated at the time of choice are typically interpreted as reflecting predictions regarding the outcomes associated with the different choice alternatives. However, these signals could instead reflect comparisons between the presented choice options and previously presented choice alternatives. In the second part of the paper, we examine how value signals have been successfully dissociated from saliency related signals, such as attention, arousal and motor preparation in studies employing outcomes with both positive and negative valence. We hope that highlighting these issues will prove useful for future studies aimed at disambiguating the contribution of different neuronal populations to choice behavior.